2015
DOI: 10.3389/fmicb.2015.00136
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric CO2 levels affect community structure of rice root-associated bacteria

Abstract: A number of studies have shown that elevated atmospheric CO2 ([CO2]) affects rice yields and grain quality. However, the responses of root-associated bacteria to [CO2] elevation have not been characterized in a large-scale field study. We conducted a free-air CO2 enrichment (FACE) experiment (ambient + 200 μmol.mol−1) using three rice cultivars (Akita 63, Takanari, and Koshihikari) and two experimental lines of Koshihikari [chromosome segment substitution and near-isogenic lines (NILs)] to determine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 39 publications
6
17
0
Order By: Relevance
“…A parallel study to the present study demonstrated that the abundance of methane-oxidizing bacteria in rice roots decreased under elevated [CO 2 ], which interacted with elevated soil temperature in the paddy field (31). The results of the present study demonstrated that a similar effect occurred in bulk soil.…”
Section: Discussionsupporting
confidence: 61%
“…A parallel study to the present study demonstrated that the abundance of methane-oxidizing bacteria in rice roots decreased under elevated [CO 2 ], which interacted with elevated soil temperature in the paddy field (31). The results of the present study demonstrated that a similar effect occurred in bulk soil.…”
Section: Discussionsupporting
confidence: 61%
“…Recent studies have revealed only minor changes in soil microbial communities under eCO 2 [8]. But it is important to understand microbial response to increasing (CO 2 ) to predict its effects on soil as plant-associated microbes produce plant hormones, fix nitrogen, and oxidize methane [9].…”
Section: Introductionmentioning
confidence: 99%
“…Das and Adhya (2012) noted that an increase of methanogenic population with elevated CO 2 levels was the most important reason for enhanced CH 4 production under CO 2 enrichment. In a free air CO 2 enrichment (FACE) experiment, Okubo et al (2015) also found that the number of copies of the mcrA gene significantly increased when CO 2 concentrations were elevated in rice paddy fields. Similarly, our results showed that elevated CO 2 concentrations significantly increased the abundance of methanogens in the rice rhizosphere soil ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 94%